Why combine diet and physical activity in the same international research society? - Baranowski Tom (BMC, 2004)
Abstract Research in diet and physical activity in the U.S. started in very different traditions, with behavioral science input being uneven in their development. Investigators and policy makers in Europe have recognized the complementarity of diet and physical activity and incorporated them both under the label Public Health Nutrition. Joining these disciplines internationally offers the opportunity to benefit all, since the problems addressed are human, not specific to any one country. In regard to why combine diet and physical activity, at the biological level, there is reason to believe that diet and physical activity working in concert can remodel physiological structures and processes toward healthful ends. The diet and physical activity behaviors themselves vary in characteristics and are similar in others. The behavioral science components of these two disciplines face similar problems, and can learn from the advances made by the other, in the areas of measurement, correlates and intervention. By working together, knowledge will be enhanced from uncovering complementary and interactive relationships between diet and physical activity, and in relation to disease risks, that may result in designing more effective and efficient interventions and policies. Since the behavioral sciences are at a disadvantage in comparison to the biological sciences in terms of scientific advances and thereby capturing the popular imagination for solutions to health problems, we must redouble our efforts to enhance funding for behavioral research in regard to diet and physical activity and to make the research advances necessary to prevent the medicalizing of essentially social and behavioral problems. Nutrition and physical activity should most effectively do this together.